2011
DOI: 10.1007/s11136-010-9843-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between quality of life and anxiety symptoms and the moderating effects of socio-demographic characteristics in Taiwanese adolescents

Abstract: Anxiety symptoms require intervention when developing strategies to improve the QOL of adolescents. Meanwhile, clinicians should take socio-demographic characteristics into consideration when working on QOL issues and anxiety symptoms in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The findings of this study overlap with the previous results Dubayova et al, 2013;Mark Hyman, Clary, Fayyad, & Endicott, 2005;Ntoumanis & Biddle, 1998;Yen et al, 2011;Zakaria, Zain, Ahmad, & Erlina, 2012). However, the structural equation model created in this study should be enriched by the addition of different variables.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The findings of this study overlap with the previous results Dubayova et al, 2013;Mark Hyman, Clary, Fayyad, & Endicott, 2005;Ntoumanis & Biddle, 1998;Yen et al, 2011;Zakaria, Zain, Ahmad, & Erlina, 2012). However, the structural equation model created in this study should be enriched by the addition of different variables.…”
Section: Discussionsupporting
confidence: 71%
“…This result demonstrated that a model of mathematics education quality perception, anxiety and achievement can be created. The finding of the studies, which indicate the relationships between quality perception and anxiety (Dubayova et al, 2013;Mark Hyman, Clary, Fayyad, & Endicott, 2005;Yen et al, 2011) and anxiety and achievement Ntoumanis & Biddle, 1998;Zakaria, Zain, Ahmad, & Erlina, 2012), demonstrate that mathematics education quality perception is one of the significant determinants of mathematics anxiety and achievement and supports the generation of the resulting model.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have consistently shown an independent association of both conditions with QoL in adulthood 34,35 ; however, little evidence for independent negative effects of GAD and MD on QoL in adolescence are available in the literature. A previous study 12 showed a mediation role of some proximal variables, such as demographics, in the association between anxiety and adolescent QoL, also demonstrating independent significant associations. However, to the best of our knowledge, the present study is the first to demonstrate that anxiety and depression are strongly associated with QoL independently of other proximal variables, such as childhood abuse/neglect and family dysfunction (both of which are strong predictors of childhood anxiety).…”
Section: Discussionmentioning
confidence: 74%
“…7 Finally, it is widely acknowledged that mental disorders affect QoL in childhood and adolescence. 8 Anxiety disorders have been associated with QoL in adulthood, [9][10][11] however, few studies have explored this association in adolescence, 12 and even fewer have investigated independent associations of different conditions that affect both anxiety disorders and QoL, such as childhood maltreatment and psychosocial distress in the family environment. 6,13 Therefore, it is unclear whether anxiety symptoms influence QoL independently or whether they influence other proximal variables that are associated with QoL in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The current study also examined subtypes of anxiety in relation to QOL, making a novel contribution to a small literature, which has only examined global measures of anxiety in association with QOL. 44,45 When all 4 anxiety subscales were entered into models simultaneously, while controlling for demographic variables and externalizing symptomatology, physical symptoms and social anxiety demonstrated significant associations with parent-reported QOL. The finding of associations between QOL and both anxiety-related physical symptoms and social anxiety symptoms was expected, as it is in keeping with prior literature.…”
Section: Discussionmentioning
confidence: 99%